The archivist facing the challenge: classification and archiving of tattoos as specific forms of archival documents - Petrič, Gregor (Atlanti +, 2022)
The present study, based on four published articles (Sundberg, Kjellman (2017); Wright (2009); Calano (2012) and Dyvik, Welland (2018)), attempts to find answers to two fundamental questions: How is it possible to organise tattoos as a modern form of records and whether, given their specifics, it is possible to archive them? Present- ing some organisational solutions offered by the above papers dealing with tattoos of Russian and Soviet prisoners, Polynesian and Filipino natives, and American Iraqi and Afghan war veterans, the author disputes the widespread use of the term ‘body as archive’ as scholarly inadequate and metaphorical at best. He finds several ways to classify tattoos, exposing the aboriginal connotative model as the only one capable of representing tattoos in their entirety, which is a prerequisite for accurate description in the archival process.
Keywords: archiving expose; classification; connotation; record; tattoo